Směnka jako platební instrument (ekonomické a právní aspekty) - Geryková, Aneta (2006)
The bill of exchange as a payment instrument (economic and legal aspects) The main themes of my graduation thesis are signatures of parties to a bill. Next capitols are about bill process-legal aspect and use of bill of exchange in banking system-economic aspect.